Access to bank finance for UK SMEs in the wake of the recent financial crisis. Issue 6 (5th September 2016) - Cowling, Marc; Liu, Weixi; Zhang, Ning
Abstract : Purpose: The purpose of this paper is to investigate how entrepreneurs demand for external finance changed as the economy continued to be mired in its third and fourth years of the global financial crisis (GFC) and whether or not external finance has become more difficult to access as the recession progressed. Design/methodology/approach: Using a large-scale survey data on over 30, 000 UK small- and medium-sized enterprises between July 2011 and March 2013, the authors estimate a series of conditional probit models to empirically test the determinants of the supply of, and demand for external finance. Findings: Older firms and those with a higher risk rating, and a record of financial delinquency, were more likely to have a demand for external finance. The opposite was true for women-led businesses and firms with positive profits. In general finance was more readily available to older firms post-GFC, but banks were very unwilling to advance money to firms with a high-risk rating or a record of any financial delinquency. It is estimated that a maximum of 42, 000 smaller firms were denied credit, which was significantly lower than the peak of 119, 000 during the financial crisis. Originality/value: This paper provides timely evidence that adds to the general understanding of what really happens in the market for small business financing three to five years into an economic downturn and in the early post-GFC period, from both a demand and supply perspective. This will enable the authors to consider what the potential impacts of credit rationing on the small business sector are and also identify areas where government action might be appropriate.